2009
DOI: 10.1051/epjap/2009032
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal spectroscopic evaluation of ultra violet-irradiated mouse skin inflammatory and precancerous stages: instrumentation, spectral feature extraction/selection and classification (k-NN, LDA and SVM)

Abstract: et al.. Bimodal spectroscopic evaluation of ultra violet-irradiated mouse skin inflammatory and precancerous stages: instrumentation, spectral feature extraction/selection and classification (k-NN, LDA and SVM).Abstract. This paper deals with the development and application of in vivo spatially-resolved bimodal spectroscopy (AutoFluorescence AF and Diffuse Reflectance DR), to discriminate various stages of skin precancer in a pre-clinical model (UV-irradiated mouse): Compensatory Hyperplasia CH, Atypical Hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Our spatially resolved bimodal spectroscopy system has already been described in detail elsewhere (20)(21)(22). In the present study, we used seven AF excitation peaks ranging from 360 to 440 nm and a wide wavelength band (330-720 nm) for DR.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…Our spatially resolved bimodal spectroscopy system has already been described in detail elsewhere (20)(21)(22). In the present study, we used seven AF excitation peaks ranging from 360 to 440 nm and a wide wavelength band (330-720 nm) for DR.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…Therefore, fusing the two types of optical information gets a wider insight into the skin modi-fications. In a second published study [20], our team showed how spatial resolution (the use of several distances between excitation and collection optical fibers) increases diagnosis accuracy as well as the fact that SVM is the most appropriate classification algorithm to our problem at hand (still in a pairwise approach with a priori knowledge on the data) acquired through a bimodal approach. In order to get closer to medical interest, we propose in the current study to process data obtained through a spatially-resolved bimodal approach first, with no a priori knowledge of the data set (no extraction of spectral features based on spectra visualization) and second, to base our SVM-classification on a multi-class approach (instead of a decomposition scheme).…”
Section: Introductionmentioning
confidence: 99%
“…The validation of our approach is based on a preprocessed spectroscopic data set acquired on mice skin healthy and hyperplastic and dysplastic tissues in the framework of a preclinical UV-induced carcinogenesis study already presented in details together with the experimental set-up in Amouroux et al 1 and Diaz et al 16 . This latter data set corresponds to a multidimensional matrix containing a total of 252 tissue sites, each site being characterized by (i) seven AF intensity spectra (corresponding to seven narrow-band wavelength excitations) and shaped into Emission-Excitation Matrices (EEM), (ii) one DR spectrum (obtained for a large-band wavelength illumination) and (iii) the histological class determined by the histopathological analysis (considered as gold standard classification).…”
Section: Methodsmentioning
confidence: 99%
“…Our works are focused on the combination of steady-state and spatially resolved Diffuse Reflectance (DR) spectroscopy and multiple excitation AutoFluorescence (AF) spectroscopy to improve diagnosis efficiency of skin precancerous tissues 1,10,11 . For simplicity and cost effective instrumentation considerations, steadystate excitation and spatial resolution are preferred 16 . A multiple optical fiber-probe is then used in which several collecting fibers at different distances from one excitation fiber (CEFS, Collection to Excitation Fiber Separation) are selected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation